Effects of extensor synovectomy and excision of the distal ulna in rheumatoid arthritis on long-term function. - Jain, A; Ball, C; Freidin, A; Nanchahal, J (2010)
PURPOSE: Objective outcomes data after excision of the distal ulna in rheumatoid arthritis are lacking. The aim of this study was to evaluate the functional results of this surgery in the long term. METHODS: We prospectively collected data on range of motion (22 wrists), visual analog pain scores (14 wrists), and grip strength measured using a Jamar dynamometer (20 hands) in a group of 23 patients (26 wrists) preoperatively and at 3 months, 12 months, and a minimum of 5 years postoperatively (range, 5.3-10.4 y). The Jebsen-Taylor hand function test was administered to 9 patients at the same time points. A subgroup of patients also underwent extensor carpi radialis longus to extensor carpi ulnaris tendon transfer (11 wrists). RESULTS: At one year, there were improvements in wrist pronation and supination, which were maintained at final follow-up. Active radial deviation decreased significantly at 3 months (p = .01) and one year (p = .02); this remained reduced at final follow-up (not significant). Wrist extension and active ulnar deviation showed slight improvements by one year, but reduced to levels below that measured preoperatively by final follow-up. Wrist flexion was significantly reduced at all time points postoperatively. Grip strength showed improvement from 10.0 kg (standard deviation [SD] 4.1 kg) preoperatively to 12.5 kg (SD 4.6 kg) 1 year after surgery and returned to preoperative levels (9.5 kg, SD 5.6 kg) by final follow-up. Wrist pain was significantly reduced from a mean score of 5 (SD 4) preoperatively to 2 (SD 2) postoperatively (p = .01). The Jebsen-Taylor hand function test showed improvements in writing and card turning. CONCLUSIONS: In the long term, excision of the distal ulna in rheumatoid patients results in an improvement in some aspects of hand function. There is a significant (p = .01) reduction in wrist pain but a reduction of wrist flexion. TYPE OF STUDY/LEVEL OF EVIDENCE: Therapeutic IV.